Detection of Genuine and Posed Facial Expressions of Emotion: Databases and Methods - Jia, Shan; Wang, Shuo; Hu, Chuanbo; Webster, Paula J.; Li, Xin (Frontiers in Psychology, 2021)
Facial expressions of emotion play an important role in human social interactions. However, posed acting is not always the same as genuine feelings. Recent research has found that facial expressions are increasingly used as a tool for decoding social interactions instead of personal emotions. Therefore, the credibility assessment of facial expressions, namely, the discrimination of genuine (spontaneous) expressions from posed (deliberate/volitional/deceptive) ones, is a crucial yet challenging task in facial expression understanding. With recent advances in computer vision and machine learning techniques, rapid progress has been made in recent years for automatic detection of genuine and posed facial expressions. This paper presents a general review of the relevant research, including several spontaneous vs. posed (SVP) facial expression databases and various computer vision-based detection methods. In addition, a variety of factors that will influence the performance of SVP detection methods are discussed along with open issues and technical challenges in the nascent field.